Modelling of electric fields at mid-range locations for upward lightning at the Sentech tower, South Africa - Smit, Jason Ronald (My University, 2022)
This research compares the transmission line, modified transmission line linear and modified transmission line exponential models to determine the bested suited model for simulating the electric field at mid ranges (2 km to 10 km). The current and results electric fields for lightning events to the Sentech tower, in Johannesburg South Africa, are used as the primary data. Data from the 2020-2021 lightning season is presented, analysed and compared to similar work done in other regions. There were a total of 42 lightning events during the season. Measurements showed agreement with measurements made in Europe and Japan for peak current distribution, charge transfer and inter-stroke time distribution. However, the measurements showed a multiplicity which is twice that seen in Austria and Japan. Two of the measured flashes were used to simulate and compare remote electric fields to measurements at 2 km and 6 km. The two flashes had a total of 26 subsequent return strokes and 5 initial current fast pulses. The electric field simulations show a strong linear relationship for the initial peak current for measured and simulated values across return stroke models. This relationship increases as the contribution of the electrostatic component becomes less (over increases distance). The modified transmission line exponential model however, performed best when reproducing the electric field waveform characteristics.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Electrical Engineering to the Faculty of Engineering and the Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2022